Coexistence of p16/CDKN2A homozygous deletions and activating EGFR mutations in lung adenocarcinoma patients signifies a poor response to EGFR-TKIs. (December 2016) - Jiang, Juhong; Gu, Yingying; Liu, Jing; Wu, Ruibin; Fu, Lin; Zhao, Jin; Guan, Yubao
Highlights: P16 HDs were detected in 24.4% of lung adenocarcinomas before EGFR-TKI therapy. P16 HDs correlated with a shorter median PFS in response to EGFR-TKIs. P16 HDs may predict response to EGFR-TKI therapy in lung adenocarcinoma patients. Abstract: Objectives: Activating mutations in the epidermal growth factor receptor (EGFR) are strongly predictive of EGFR-tyrosine kinase inhibitor (TKI) activity in non-small cell lung cancer (NSCLC). However, primary resistance to EGFR-TKIs occurs in approximately 20–30% of NSCLC patients with EGFR mutations. The goal of this study was to determine whether p16/CDKN2A homozygous deletion (HD) is associated with primary resistance to EGFR-TKIs in lung adenocarcinoma patients with EGFR activating mutations. Methods: We investigated 127 patients with stage IIIB or IV lung adenocarcinoma harboring activating EGFR mutations, and who had received EGFR-TKIs as first-line therapy. Dual-color fluorescence in situ hybridization for p16/CDKN2A and chromosome 9 was performed in tumor biopsy samples obtained before initiation of EGFR-TKI treatment. Results: p16/CDKN2A HD was detected in 24.4% (31/127) of patients, and the overall response rate in patients with and without this mutation was 48.4% and 78.1%, respectively (P = 0.0027). The median progression-free survival was 5.3 months (95% confidence interval [CI]: 4.582–6.018) for patients with p16/CDKN2A HD and 10.5 months (95% CI: 9.365–11.635 months) for patients without the mutation (P = 0.001). No correlations between p16/CDKN2A HD and patient characteristics including gender, age, smoking history, EGFR mutation type, tumor-node-metastasis stage, and performance status were found. Conclusions: Our study demonstrates that the coexistence of p16/CDKN2A HDs and activating EGFR mutations in lung adenocarcinoma patients signifies a poor response to EGFR-TKI therapy.